2020
DOI: 10.1021/acssynbio.0c00312
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting a Phosphite Dehydrogenase/Formamidase-Driven Antimicrobial Contamination System in Bacillus subtilis for Nonsterilized Fermentation of Acetoin

Abstract: Microbial contamination, especially in large-scale processes, is partly a life-or-death issue for industrial fermentation. Therefore, the aim of this research was to create an antimicrobial contamination system in Bacillus subtilis 168 (an ideal acetoin producer for its safety and acetoin synthesis potential). First, introduction of the formamidase (FmdA) from Helicobacter pylori and the phosphite dehydrogenase (PtxD) from Pseudomonas stutzeri enabled the engineered Bacillus subtilis to simultaneously assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…A previous study had similarly found that ptxD from P. stutzeri was better than other genes that were tested in B. subtilis . 23 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study had similarly found that ptxD from P. stutzeri was better than other genes that were tested in B. subtilis . 23 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study had similarly found that ptxD from P. stutzeri was better than other genes that were tested in B. subtilis. 23 Because the original Cg-0206 strain could not grow on the Pt medium, a conventional Pi fermentation medium (Pi medium) but without CSL was used to determine its growth. As shown in Figure 1B, the growth of Cg-0206 was reduced by 35.0% (from 5.03 to 3.27 cfu/mL) and L-lysine production was reduced by 35.6% (from 38.33 to 24.67 g/L after 72 h, Figure 1C) by omitting CSL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept has been an effective selection method for prokaryotic and eukaryotic microbial hosts that do not use antibiotics [ 17 , 18 ]. In particular, the cheap availability of Pt offers distinct practical benefits: an industrial fermentation process without the requirement of sterilization of nutrient broth [ 19 , 20 , 21 ] and economically viable selective microbial cultivation at large scales [ 21 , 22 ]. Previously, we and others reported the implementation of a Pt-based selective cultivation method for cyanobacteria and several other microalgae [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%